Maternal and paternal preconception exposure to phenols and preterm birth. (April 2020) - Mustieles, Vicente; Zhang, Yu; Yland, Jennifer; Braun, Joseph M.; Williams, Paige L.; Wylie, Blair J.; Attaman, Jill A.; Ford, Jennifer B.; Azevedo, Alexandra; Calafat, Antonia M.; Hauser, Russ; Messerlian, Carmen
Highlights: Prenatal exposure to some phenols was previously associated with preterm birth. Parental preconception exposure and preterm birth risk is understudied. Maternal preconception BPA and BPS exposure increased risk of singleton preterm birth. Fathers preconception paraben exposure may be associated with preterm birth. Preconception phenol exposure may be an unrecognized risk factor for preterm birth in subfertile couples. Abstract: Background: Phenol exposure during pregnancy has been associated with preterm birth, but the potential effect of preconception exposure in either parent is unknown. There is a growing body of evidence to suggest that the preconception period is a critical window of vulnerability for adverse pregnancy outcomes. Objective: We examined whether maternal and paternal preconception urinary concentrations of select phenols were associated with the risk of preterm birth among couples attending fertility care. Methods: The analysis included 417 female and 229 male participants of the Environment and Reproductive Health (EARTH) Study who gave birth to 418 singleton infants between 2005 and 2018 and for whom we had phenol biomarkers quantified in at least one urine sample collected before conception. Mothers and fathers provided an average of 4 and 3 urine samples during the preconception period, respectively. We calculated the geometric mean of bisphenol A (BPA), bisphenol S (BPS), benzophenone-3, triclosan, and the molar sum of parabens (ΣParabens) urinary concentrations to estimate each participant's preconception exposure. Risk ratios (RRs) of preterm birth (live birth before 37 completed weeks' gestation) were estimated using modified Poisson regression models adjusted for covariates. Results: The mean (SD) gestational age among singletons was 39.3 (1.7) weeks with 8% born preterm. A natural log-unit increase in maternal preconception BPA (RR 1.94; 95% CI: 1.20, 3.14) and BPS (RR 2.42; 95% CI: 1.01, 5.77) concentration was associated with an increased risk of preterm birth. These associations remained after further adjustment for maternal prenatal and paternal preconception biomarker concentrations. Paternal preconception ΣParabens concentrations showed a possible elevated risk of preterm birth (RR 1.36; 95% CI: 0.94, 1.96). No consistent pattern of association was observed for benzophenone-3 or triclosan biomarkers in either parent. Discussion: Maternal preconception urinary BPA and BPS concentrations, as well as paternal preconception urinary parabens concentrations were prospectively associated with a higher risk of preterm birth. Subfertile couples' exposure to select phenols during the preconception period may be an unrecognized risk factor for adverse pregnancy outcomes.